Distribution and concentration of linear alkylbenzenes in river sediments and short-neck clams (Paphia undulata) in Peninsular Malaysia - Magam, Sami Muhsen Sleman (2018)
Due to population growth and extensive urbanization in recent years, urban wastewater has entered to the rivers and coastal environment in Peninsular Malaysia, causing risks to human health and posing threats to other organisms. Therefore, tracing regional anthropogenic influences is important for assessing the magnitude of pollution caused by human activities and its consequences to the environment, especially aquatic ecosystems. In the present study, the presence of linear alkylbenzenes (LABs) that can be used as sawage indicator in equatic enviroment was examined in sediments and short-neck clams (Paphia Undulata) tissue. This study aimed to investigate the distribution, concentration and composition of LABs, and also degradation of LABs with the emphasis on the role of bioavailability of LABs to P. undulata from sediments and dissipating LABs from input sources to remote areas. Sediment samples were collected from selected rivers and estuaries from the Kedah, Merbok, Prai, Perak, Kiang Melaka, Segget, Kuantan, Terengganu, and Kelantan, while P. undulata samples were taken from the Kedah, Merbok, Prai, Perak, Kiang and Melaka Estuaries in Peninsular Malaysia from January 2013 to February 2014. The sediments and P. undulata samples were homogenized, freeze-dried, extracted, cleanup, fractionated and analyzed using gas chromatography mass spectrometry (GC-MS). The concentrations of total LABs in sediments varied from 55.22 to 3117.16 ng g -I dry weight (dw) and P. undulata varied from 21.09 to 861.65 ng g -I dw. LABs in sediments can be classified as low to moderate (55.22 to 313.69 ng g -I) contamination in the Kedah, Kuantan, Perlis, Merbok, Kelantan, Terengganu and Perak, moderate to high (977.81 to 1,427.37 ng g -I) in the Segget, and Melaka and high to very high (2,909.59 to 3,117.16 ng g -I) in the Prai and Klang Rivers and Estuaries. LABs in the soft tissues of P. undulata can be classified as moderate contamination in the Kedah and Melaka, low contamination in the Perak and Merbok and high contamination in the Prai and Klang. The compositional profiles of LABs in sediments and P. undulata of the studied areas demonstrated that the levels oflong chain alkylbenzenes (CI3; 33 %) were higher than short chain alkylbenzenes (CI0; 11 %). The results from the ratio of internal (I) and external (E) isomers of LABs (UE ratios), in the surface sediments were from 0.56 to 3.18, while the results from IIE ratios in P. undulata were from 0.70 to 3.21 indicating a range of raw, primary to secondary treated sewage effluents. The values of the ratio of 5-CnLAB+5-CI2LAB relative to 5-CIlLAB+5-CIOLAB (US ratio) ranged from 1.04 to 4.03 in the sediments and from 0.87 to 4.87 in (P. undulata). Meanwhile, the values of the ratio of6-,5-,4-,3-and 2-C13/6-, 5-, 4-, 3-, and 2-CI2LAB (CdCl2 ratio) ranged from 1.14 to 3.54 in the sediments and from 2.23 to 4.78 in P. undulata in the coastal areas of Peninsular Malaysia. These values are slightly higher than those of the commercial detergents. There was significant correlation (r = 94, p < 0.05) between total parent LABs in sediments and in P. undulata which indicated the ability of P. undulata to accumulate the LABs. Therefore, P. undulata can be considered as a good biomonitor of LABs in the aquatic environment. Based on the results from the LABs concentrations, it is recommended that different sites of Malaysia should be monitored and managed to reduce the levels of LABs entering the aquatic environment.